Inhibitory effects of copper-aspirin complex on platelet aggregation - Shen Zhi-Qiang; Chen Zhi-He; Ma Guo-Yi; Wang De-Cheng; Wu Wan-Ling; Liu Wei-Ping; Yang Yi-Kun; Xiong Hui-Zhou (Acta Pharmacologica Sinica; Vol 18, No 4 (July 1997): Acta Pharmacologica Sinica, 2016)
AIM: To study the inhibitory effects of copper-aspirin complex (CuAsp) on platelet aggregation. METHODS: With adenosine diphosphate the effects of CuAsp on platelet aggregation in vitro or in vivo were investigated. Radioimmunoassay and fluorophotometry were used to measure thromboxane B2 (TXB2) generation from platelets, the levels of TXB2 and of 6-keto-PGF1 alpha in plasma and the platelet serotonin release reaction. RESULTS: In vitro, CuAsp inhibited arachidonic acid (AA)-induced aggregation (IC50 = 17 mumol.L-1, 95% confidence limits: 9-33 mumol.L-1), the release of 5-HT (IC50 = 19 mumol.L-1, 95% confidence limits: 10-30 mumol.L-1), and TXB2 generation from platelets (P < 0.05). CuAsp 10 mg.kg-1 i.g. selectively inhibited AA-induced aggregation, and increased the 6-keto-PGF1 alpha concentration in plasma while decreased that of TXB2. CONCLUSION: CuAsp, in vitro or in vivo, shows more potent inhibitory effects on AA-induced aggregation than aspirin (Asp), related to the inhibition of platelet cyclooxygenase and the release of active substances from platelets.